2014
DOI: 10.3126/ajms.v6i4.11257
|View full text |Cite
|
Sign up to set email alerts
|

Distribution pattern of ABO and Rh blood groups and their allelic frequencies among different ethnic groups in Malaysia

Abstract: Background: The experiment involved 4 different racial populations such as Malay (M), Chinese (C), Indian Tamil (I) and confounded population termed as Others (O) from 13 states and 1 federal territory in Malaysia.Methods: A total of 1101 students in Universiti Malaysia Kelantan were surveyed for ABO blood type and Rh factor.Results: Phenotypic frequencies were 0.24, 0.27, 0.09 and 0.40 in M; 0.26, 0.21, 0.06 and 0.38 in C; 0.27, 0.31, 0.09 and 0.33 in I and 0.11, 0.29, 0.09 and 0.51 in O for A, B, AB and O bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…As per the findings of the current study, Rh-D positive blood group was the most predominant accounting for 90.5% and the rest 9.5% was Rh-D negative. This is relatively similar to the study of Akinnuga et al, (2011) done in Elele, Nigeria where rhesus D-positive individuals constituted 91.7%. The finding was also in agreement with research done in the United States by Garratty et al, (2004) among different ethnic groups, where rhesus D positive was the highest at 90.3% and rhesus D negative was the lowest at 9.7%.…”
Section: Discussionsupporting
confidence: 88%
“…As per the findings of the current study, Rh-D positive blood group was the most predominant accounting for 90.5% and the rest 9.5% was Rh-D negative. This is relatively similar to the study of Akinnuga et al, (2011) done in Elele, Nigeria where rhesus D-positive individuals constituted 91.7%. The finding was also in agreement with research done in the United States by Garratty et al, (2004) among different ethnic groups, where rhesus D positive was the highest at 90.3% and rhesus D negative was the lowest at 9.7%.…”
Section: Discussionsupporting
confidence: 88%
“…Although ABO/Rh blood groups are determined at conception and remain throughout life, diverging phenotypic results have been obtained across various ethnic populations in different geographical boundaries. [3][4][5][6][7] In addition to the importance of these blood groups in blood transfusion, their usefulness in population genetic studies, population migration patterns, forensics and disputed paternity cases is well established. 8,9 Moreover, there are several reports in which some associations have been found for diseases between the ABO and Rh blood group systems.…”
Section: Introductionmentioning
confidence: 99%
“…On comparing allele frequencies of different studies world-wide [24,25,[29][30][31][32], we found that allele frequency of I O in ABO & I D in Rh blood group system is highest across the world (Table 6). Thus our findings are similar to other studies.…”
Section: Discussionmentioning
confidence: 99%